Micrografting provides evidence for systemic regulation of sulfur metabolism between shoot and root - Forieri, Ilaria; Aref, Rasha; Wirtz, Markus; Hell, Rüdiger (Plants, 2021)
The uptake of sulfate by roots and its reductive assimilation mainly in the leaves are not only essential for plant growth and development but also for defense responses against biotic and abiotic stresses. The latter functions result in stimulus-induced fluctuations of sulfur demand at the cellular level. However, the maintenance and acclimation of sulfur homeostasis at local and systemic levels is not fully understood. Previous research mostly focused on signaling in response to external sulfate supply to roots. Here we apply micrografting of Arabidopsis wildtype knock-down sir1-1 mutant plants that suffer from an internally lowered reductive sulfur assimilation and a concomitant slow growth phenotype. Homografts of wildtype and sir1-1 confirm the hallmarks of non-grafted sir1-1 mutants, displaying substantial induction of sulfate transporter genes in roots and sulfate accumulation in shoots. Heterografts of wildtype scions and sir1-1 rootstocks and vice versa, respectively, demonstrate a dominant role of the shoot over the root with respect to sulfur-related gene expression, sulfate accumulation and organic sulfur metabolites, including the regulatory compound O-acetylserine. The results provide evidence for demand-driven control of the shoot over the sulfate uptake system of roots under sulfur-sufficient conditions, allowing sulfur uptake and transport to the shoot for dynamic responses.
Gesehen am 30.09.2021